2018
DOI: 10.2478/jce-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With in-Hospital Death in Patients with Acute Mesenteric Artery Ischemia

Abstract: Objective: The aim of the study was to assess the factors associated with increased mortality in patients with acute mesenteric ischemia, emphasizing the importance of an early diagnosis and a prompt surgical intervention in order to avoid lesion progression. Materials and method: A retrospective analytical study was conducted on a study population of 50 male and female patients with acute ischemia of the mesenteric arteries, aged between 36-92 years. Demographic and pathological history characteristics were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Several studies suggest the time from admission to theatre for source control is a critical determinant for survival in acute abdominal pathology. Élthes and colleagues (2018) 25 compared deceased patients with survivors in their cohort study, finding a mean time from admission to theatre of 9.10 hours compared with 5.57 hours respectively. Four studies suggested a reduced survival of 2.2–3 per cent with each additional hour of delay from admission to surgery 19 , 21 , 24 , 28 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies suggest the time from admission to theatre for source control is a critical determinant for survival in acute abdominal pathology. Élthes and colleagues (2018) 25 compared deceased patients with survivors in their cohort study, finding a mean time from admission to theatre of 9.10 hours compared with 5.57 hours respectively. Four studies suggested a reduced survival of 2.2–3 per cent with each additional hour of delay from admission to surgery 19 , 21 , 24 , 28 .…”
Section: Resultsmentioning
confidence: 99%
“…This compared with only 14 of 219 (6.1 per cent) patients having a delayed diagnosis when there was no delay in imaging 5 . Élthes and co-workers (2018) 25 found that, regarding acute mesenteric ischaemia (AMI), the more prolonged the investigation period in the ED, the greater the lesion progression. This was directly associated with an increase in mortality rate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations